Altered theta–beta ratio in infancy associates with family history of ADHD and later ADHD‐relevant temperamental traits. (20th February 2022) - Begum‐Ali, Jannath; Goodwin, Amy; Mason, Luke; Pasco, Greg; Charman, Tony; Johnson, Mark H.; Jones, Emily J.H.; ,
Abstract : Background: Uncovering the neural mechanisms that underlie symptoms of attention deficit hyperactivity disorder (ADHD) requires studying brain development prior to the emergence of behavioural difficulties. One new approach to this is prospective studies of infants with an elevated likelihood of developing ADHD. Methods: We used a prospective design to examine an oscillatory electroencephalography profile that has been widely studied in both children and adults with ADHD – the balance between lower and higher frequencies operationalised as the theta–beta ratio (TBR). In the present study, we examined TBR in 136 10‐month‐old infants (72 male and 64 female) with/without an elevated likelihood of developing ADHD and/or a comparison disorder (Autism Spectrum Disorder; ASD). Results: Infants with a first‐degree relative with ADHD demonstrated lower TBR than infants without a first‐degree relative with ADHD. Further, lower TBR at 10 months was positively associated with temperament dimensions conceptually related to ADHD at 2 years. TBR was not altered in infants with a family history of ASD. Conclusions: This is the first demonstration that alterations in TBR are present prior to behavioural symptoms of ADHD. However, these alterations manifest differently than those sometimes observed in older children with an ADHD diagnosis. Importantly, altered TBR was not seen in infants at elevated likelihood of developing ASD, suggesting a degree of specificity to ADHD. Taken together, these findings demonstrate that there are brain changes associated with a family history of ADHD observable in the first year of life.